Types of activity of a judge at the preparatory stage to court hearings - O. M. Tsilmak (Law and Safety)
It has been noted that the reform of the judicial and legal system is undergoing in Ukraine. Its main objective is to update the judicial branch of power to restore confidence in the court. Judicial activity is quite complex and multifunctional. Therefore, the personality of a judge, his level of qualification, competence and professionally important characteristics are of great importance for this activity.